Immunology and genetics in nonhuman primates: Study of KIR3DL02 interaction with MHC-class-I ligands of rhesus macaques - Jesus, Kátia Ribeiro de (2018)
Dissertação de Mestrado em Investigação Biomédica apresentada à Faculdade de Medicina